POTENSI PSEUDOMONAS AERUGINOSA SEBAGAI AGENS BIOKONTROL TERHADAP SCLEROTIUM ROLFSII SACC. DAN BIOSTIMULAN PADA TANAMAN KEDELAI - KHALIMI, KHAMDAN; RAKA, I GUSTI NGURAH; SIADI, I KETUT (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011), 2012)
Potential of Pseudomonas aeruginosa as Biological Control Agents against Sclerotium rolfsii Sacc. and Biological Stimulants on Soybean Plant. The objectives of this experiment were conducted to evaluate the effectiveness ofP. aeruginosa as an agent of biological control and biological stimulants. P. aeruginosawere tested for antagonistic activity against Sclerotium rolfsii Sacc. The test for antagonistic activity by bacteria was done through side by side culture. Soybean seeds that will be used in the rhizobacteria treatment were soaked in rhizobacteria suspension for 15 minutes. For wihout the treatment, seeds soaked with sterile water instead of rhizobacteria suspension. Results of this experiment,P. aeruginosa showed strong inhibitory activity againstS. rolfsii Sacc. on PDA medium. Percentage of inhibitory activity was 94,4%. Application of P. aeruginosa significantly increased the plant growth. The maximum plant hight, the maximum number of leaves, fresh and dry weights of root, fresh and dry weights of shoot, and chlorophyll content on treated plants significantly higher than those of un-treated control plants according to the Duncan’s multiple range test (P<0.05%). These results suggested that application of rhizobacteria could promote the plant growth and increase the yield.
Keywords: biological control, biological stimulants, soybean plant, Pseudomonas aeruginosa